An Application of a new Version of (G?/G)- Expansion Method - Yokus, Asif; Tuz, Munevver (Amer Inst Physics, 2017)
In this study, we develop extended (G'/G)-expansion method which is suggested in [1]. By this method, we find traveling wave solutions of nonlinear KdV and Hirota-Satsuma equations.
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE
Keywords: KdV equation; Hirota-Satsuma equation; An extended (G '/G)-expansion method; Traveling wave solution; Nonlinear partial differential equation; Exact solutions